The Debulking of Recurrent Right Testicular Seminoma with Anterolateral Thigh Flap Reconstruction - Syifa Fauziah Fadhly; Rachmat Budi Santoso; Edward Usfie Harahap; Dewi Aisiyah Mukarramah; Kasih Rahardjo Djarot; Ikhlas Arief Bramono; Rosalina Rosalina; Kardinah Kardinah; Rizky Ifandriani Putri (Indonesian Journal of Cancer, 2022)
Introduction: Radical orchidectomy is considered both a therapy and a part of the staging procedure. Stage I seminoma may be treated with orchiectomy alone while the remaining 15% to 20% may have a relapse if they receive no additional treatment during the five-year surveillance. Most recurrences occur within the first 2 years after diagnosis, and the location of the recurrence is typically in the retroperitoneum. This article aims to share the experience in the management of testicular seminoma recurrence in a multidisciplinary approach.Case Presentation: We are reporting a case of a 26-year-old male with a growing mass at the right scrotum just two months after right radical orchidectomy. This patient was previously treated with a stage I seminoma and underwent surveillance. Tumor debulking and right inguinoscrotal reconstruction using a pedicled anterolateral thigh (ALT) flap were done through collaborative surgery between urology and plastic surgery. However, according to National Comprehensive Cancer Network (NCCN), with the relapsed mass, this patient can be classified as having a stage III seminoma and considered as having a good-risk disease due to no evidence of non-pulmonary visceral metastasis. With the risk of bleomycin causing lung fibrosis, four cycles of etoposide and cisplatin can be considered the chemotherapy regimens for this patient. Evaluation after chemotherapy should be done by checking tumor markers and imaging studies.Conclusions: The reappearance of testicular seminoma in this patient unexpectedly occurred quite in a short period, that is in two months after surgery. Immediate multidisciplinary intervention by a urologist and plastic surgeon was done through tumor debulking with a wide incision margin and ALT flap reconstruction. Unfortunately, however, after the second month of follow-up, there was a bulging mass growing beneath the flap which needed further evaluation with ultrasonography to confirm the possibility of tumor recurrence or seroma. If tumor recurrence is confirmed, chemotherapy should be scheduled as soon as possible.